Studies on the Potential of Natural Zeolites and Modified Natural Zeolites Towards the Removal of Heavy Metals from Smoke Cigarette - AFZALI, M.; DARIJANI, N.; AMIRI, A. (Asian Journal of Chemistry, 2010)
In present work, the potential of natural zeolites and modified natural zeolites for removal of heavy metal cations from main stream smoke cigarette are investigated. Different natural zeolites such as clinopeltiolite, analcime, natrolite, perlite, kaolinite and bentonite have been used as filter in the cigarettes for removal of the heavy metal cations, the results have shown these natural zeolites could removed be only 0.5- 6.0 % the metal cations from mainstream cigarette. Therefore, these zeolites are modified with different substances in solid and solution state and then the potential of the modified zeolites are examined for removal of heavy metal cations from mainstream smoke cigarette. The results were shown that these modifications are suitable and modified zeolites could be removed from 13 to 47 % of heavy metal cations from mainstream smoke cigarette.